In vitro susceptibility of dermatophytes isolated from patients with end-stage renal disease: a case-control study - Marius Irimie, Alexandru Tătaru, Alexandru Oantă, Marius Moga (Berlin : Grosse Verlag, 2014)
Although the therapeutic efficacy of antifungals is well known for dermatophytosis in general population, limited data exist for patients with chronic kidney disease. The objectives of this study were to determine the dermatophyte species causing infection in patients with end-stage renal disease (ESRD) and in vitro susceptibility of isolated dermatophytes to antifungals. A total of 87 patients with ESRD who undergoing haemodialysis and 105 patients with normal renal function suspected with dermatophytosis were included. Skin scrapings or nail clippings were examined by direct microscopy and cultured on Sabouraud agar. In vitro antifungal susceptibility tests were performed using a broth microdilution method. Dermatophyte infections were identified in 32.2% of haemodialysis patients and in 29.5% of controls (P > 0.05). In both groups, Trichophyton rubrum was the most frequently isolated. Mean MIC values of the all studied antifungals for all of isolated dermatophyte strains from patients with ESRD were similar to those obtained in control group (P > 0.05). Terbinafine (TBF) had the lowest mean MIC values for all tested dermatophytes in both groups. We consider that TBF should be the treatment of choice for dermatophytosis in patients with chronic kidney disease, but the dose should be adjusted according to creatinine clearance and should be monitored for side effects.